Pengaruh Karakter Pebelajar terhadap Prestasi Akademik pada Mahasiswa Tadris IPS IAI AL-Fatimah Bojonegoro - Hidayati, Armawati; Prasetya, Sukma Perdana (Universitas Batanghari Jambi, 2024)
The purpose of this research is to determine the influence of student character in the form of intelligence level, creativity level, and achievement motivation on academic achievement. The research subjects were 32 Tadris IPS students, Tarbiyah Faculty, IAI Al-Fatimah Bojonegoro class of 2023. Data analysis was carried out using multiple regression analysis. The research results found that simultaneously and partially the variables of intelligence level, achievement motivation, and creativity level had a significant effect on academic achievement of Tadris IPS IAI AL-Fatimah Bojonegoro students